Optical coherence tomography leakage in neovascular age-related macular degeneration: Identification of choroidal neovascularization activity by location and quantification of abnormal fluid under anti-vascular endothelial growth factor therapy - Farinha, Cláudia (2021)
Optical coherence tomography leakage identified and quantified the fluid related to choroidal neovascularization activity. Low optical reflectivity change in the outer segment layer correlates with functional outcome and increasing LOR in the external layers may be a marker of early recurrence. Combining optical coherence tomography angiography and optical coherence tomography leakage allows both for choroidal neovascularization morphology and activity analysis.